5x-0.6=3

Simple and best practice solution for 5x-0.6=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-0.6=3 equation:


Simplifying
5x + -0.6 = 3

Reorder the terms:
-0.6 + 5x = 3

Solving
-0.6 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.6' to each side of the equation.
-0.6 + 0.6 + 5x = 3 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + 5x = 3 + 0.6
5x = 3 + 0.6

Combine like terms: 3 + 0.6 = 3.6
5x = 3.6

Divide each side by '5'.
x = 0.72

Simplifying
x = 0.72

See similar equations:

| 11u-84=5u | | -12n+6=-2(6n+2) | | 4-6y+3=2y+11-6y | | 2+y=1 | | 3(-2-x)=-3(-7+2x) | | 5(7)(9)=3(40+x) | | 0+y=1 | | x+2x-2x+[x(2x-2)-60]=60 | | -(-8r-6)=r+6 | | 3m+1=7-m | | 7n-16=5n-2(-8-3n) | | 0+y=2 | | -4+2(4x+4)=3+8x | | 120=.5b*15 | | x/5=-1-(-7) | | -3-3(x-3)=3x+3(3-x) | | -(1-8n)+2=1+8n | | -4+x/9=-3 | | 200=45y+45+12y-16 | | 3+2(2x-5)-10x=8+4x | | -6(x+1)-10=12+2 | | 20x^3+17x^2+3x=0 | | 15+x=3x-1 | | 8+38=86 | | -5x-10=2-1(x+4) | | 6a-2+6a=-11+1+6a+7a | | 8+38=38 | | 33x^2-108x-96=0 | | x/25=-34+29 | | 8+28=-20 | | -1.5v-3=1.3333333v-.25 | | 74-8z=2 |

Equations solver categories